The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s10509-007-9553-1
|View full text |Cite
|
Sign up to set email alerts
|

Constraint on cosmological model with matter creation using complementary astronomical observations

Abstract: The universe with adiabatic matter creation is considered. It is thought that the negative pressure caused by matter creation can play the role of a dark energy component, and drive the accelerating expansion of the universe. Using the Type Ia supernovae (SNe Ia) data, the observational Hubble parameter data, the Cosmic Microwave Background (CMB) data and the Baryonic Acoustic Oscillation (BAO) data, we make constraints on the cosmological parameters, assuming a spatially flat universe. Our results show that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The limit on the parameter β for all kinematics tests are in the range 0.50 ≤ β ≤ 1, i.e., −1 < q ≤ 0, which is acceptable range observed by SNe Ia data (Qiang et al 2007). The kinematics tests for the inflationary phase may be derived in a similar way as discussed above.…”
Section: Proper Distance-redshiftmentioning
confidence: 56%
See 1 more Smart Citation
“…The limit on the parameter β for all kinematics tests are in the range 0.50 ≤ β ≤ 1, i.e., −1 < q ≤ 0, which is acceptable range observed by SNe Ia data (Qiang et al 2007). The kinematics tests for the inflationary phase may be derived in a similar way as discussed above.…”
Section: Proper Distance-redshiftmentioning
confidence: 56%
“…Zimdahl et al (2001) tested the particle creation with SNe Ia data and got the result of accelerating universe. Recently, Qiang et al (2007) have studied the universe with adiabatic particle creation and showed that the model is consistent with SNe Ia data.…”
mentioning
confidence: 76%
“…Zimdahl et al 11 tested the particle creation with SNe Ia data and got the result of the accelerating universe. Yuan Qiang et al 12 studied the models with adiabatic particle creation and showed that the model is consistent with SNe Ia data. On a phenomenological level particle creation has been described in the literature in terms of a bulk viscous stress.…”
Section: Introductionmentioning
confidence: 86%
“…Zimdahl et al 11 tested the particle creation with SNe Ia data and got the result of the accelerating universe. Yuan Qiang et al 12 studied the models with adiabatic particle creation and showed that the model is consistent with SNe Ia data.…”
Section: Introductionmentioning
confidence: 86%
“…Recently a lot of cosmologists and astrophysicists are there addressed the FRW models with particle creation problem [48][49][50]. Zimdahl, Yuan Qiang, and their colleague [51,52] studied the models of particle creation with SN 1a data and showed the result is consistent and the universe is in an accelerating phase. At the moment, [53] is exploring a different type of matter formation.…”
Section: Introductionmentioning
confidence: 99%